Indonesian Health Law: Constitutional Mandates, Regulatory Architecture, and Contemporary Governance Challenges - Wiet Sidharta; Hargianti Dini Iswandari (International Journal of Law Analytics, 2026)
Indonesian health law must reconcile constitutional guarantees, welfare-state obligations, regulatory complexity, and contemporary governance pressures. This study aims to analyze the coherence between constitutional mandates, regulatory architecture, and health governance implementation in Indonesia. A normative juridical approach was employed through a review of constitutional provisions, statutes, regulations, and policy instruments; no respondents or informants were involved. The materials were examined using doctrinal and qualitative legal analysis. The findings show that legislative consolidation has strengthened the formal health-law framework, yet implementation remains constrained by decentralization, institutional fragmentation, weak accountability, legal uncertainty, digital-health risks, and unequal access to services. The study concludes that stronger regulatory coherence, interinstitutional coordination, and rights-based enforcement are essential to improve equitable and sustainable health governance.